Nyumba-kaya: a delicada escrevência da nação Moçambicana na obra de Mia Couto - Braúna, José Dércio (2011)
Taking literature as a privileged source of analysis this study focuses on the work of the Mozambican writer Mia Couto [1955-] seeking to analyze the problematisation about the construction of an ideology of nation that this writing allows to historiographic reflection The attention is directed toward a perception of how this author´s literary text discusses the social relations experienced in troubled times of his country´s independence in 1975 and in the conflicts that settled soon after To achieve the proposed objectives analyzes the critical view of the author in relation to political projects designed for the nation discuss their conceptions identity not essentialists as well as his imaginative rereading of the past from of the questions of his present time Another approached aspect concerns the place of this author within the literary canon of his country still in the process of formation It is a study that promotes an intensive dialogue between the historiographical work and the literary text having the theoretical reflections of post-colonial thinkers as fundament.